DIGITAL LITERACY IN TACKLING THE SPREAD OF COVID-19 IN VILLAGES - Arie Setyo Dwi Purnomo (JCES (Journal of Character Education Society), 2021)
Abstrak: Tujuan kegiatan pengabdian masyarakat ini adalah untuk memberikan pengetahuan dan kemampuan dalam mengantisipasi penyebaran covid-19. Universitas Trunojoyo  Madura melalui LPPM melaksanakan kegiatan pengabdian.  Metode yang digunakan dalam kegiatan pengabdian masyarakat ini menggunakan media webinar serta sosialisasi door to door dengan materi pola hidup bersih untuk mengantisipasi pencegahan penyebaran virus, penggunaan masker dan kebiasaan cuci tangan dengan sabun. Adapun jumlah peserta adalah 50 pemuda dan pedagang pasar pumara yang terletak di Kelurahan Mlajah Kecamatan Bangkalan Kabupaten Bangkalan. Hasil kegiatan abdimas ini agar para pemuda dan para pedagang memahami bagaimana pencegahan serta menjadi agen sosialisasi kepada lingkungan sekitar. Sehingga para pemuda dan pedagang ikut serta dalam langkah sinergis bersama pemerintah serta perguruan tinggi dalam upaya pencegahan penularan Covid-19.Abstract:  The literacy gap related to the understanding of Covid-19 prevention and health protocols in the Madurese community requires the role of the community in disseminating correct information. Youth and traders in PUMARA need to get education related to digital literacy that is easy to understand about Covid-19 and how to prevent it. This has made the basis for the LPPM Community Service Team at Trunojoyo Madura University to take part in preventing and breaking the chain of the spread of Covid-19 by providing counseling and socialization about Covid-19 to youth and traders in Mlajah village, Bangkalan sub-district, Bangkalan district through webinars and door-to-door socialization along with distribution of hand sanitizers and masks. The purpose of this activity is so that young people and traders understand how to prevent and become agents of socialization to the surrounding environment. So that young people and traders participate in synergistic steps with the government and universities in efforts to prevent the transmission of Covid-19 starting from yourself.